PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SARI HUSADA CABANG SEMARANG - Meidhita Andrie Laksono, 09.05.51.0077; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2013)
The purpose of this study to examine and analyze the effect of work motivation, organizational culture and work discipline on the performance of employees at PT. Sari Husada Semarang branch. This type of research is explanatory research or research that is explaining the study population were all employees of PT. Sari Husada Semarang branch, data collection methods used by the census to the number of respondents using as many as 80 people. Based on the analysis it can be concluded that: (1) Motivation and significant positive effect on employee performance. (2) Organizational culture is positive and significant effect on employee performance.(3) Discipline of work and significant positive effect on employee performance. The test results simultaneously work motivation, organizational culture and work discipline and significant positive effect on employee performance simultaneously. The results of the coefficient of determination of 64.3% can be explained by the work motivation, organizational culture and work discipline to performance. While the remaining 35.7% is explained by other causes beyond the variables of work motivation, organizational culture and work discipline such as leadership, salaries, work environment, training and education foremployees.Key words: work motivation, organizational culture, work discipline, employee performance.